Economic mechanisms of regulating environment ecological condition by aviation transport processes - Запорожец, А. И. (Proceedings of National Aviation University (archive), 2000)
Absence of effective economic regulators of environment protection is one of the causes of insufficient national ecological policy. The aim of economic mechanisms is to provide economic interests and motivations of the uses of the natural resources for nature protection and resources saving activity. The most effective levers are payment for environment contamination, for use of nature resources, and penalties (compensation) for violation of ecological norms and regulations